Application of the Project Method into the Teaching of the Aircraft Maintenance Vocational Subject - Hůlek, David; Vaněček, David (IEEE (Institute of Electrical and Electronics Engineers), 2019)
This article describes a project teaching method and its application into a teaching of an aircraft maintenance vocational subject. The first part of the article describes theoretical bases of this teaching method and used research methods. The used methods are basic research methods, project teaching method and questionnaire method. There is described a chosen subject in this part too. The project teaching method has been applied in this subject. The next part of the article is about a project method creation and its application in the teaching. The third part deals with a questionnaire. It is about a questionnaire creation and evaluation. The questionnaire was a source of data and information and it was a feedback for the authors too. An evaluation of all project method is mentioned in this part too. There is described a procedure of a project teaching method implementation at the end of the article. This procedure should be a support tool for teachers which want to applicate this teaching method into theirs teaching process. The main result of this work is a verification if the project teaching method can be used in such a specific subject like the aircraft maintenance vocational subject is.
Aplikace projektové metody ve výuce odborného předmětu zaměřeného na údržbu letadel
Keywords: project teaching; project method; application of the project method; aircraft maintenance; procedure of the project teaching method implementation; projektová výuka; projektová metoda; aplikace projektové výuky; údržba letadlové techniky; postup zavedení projektové výuky